PENERAPAN METODE SIMULASI UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SD INPRES 4/82 ABBUMPUNGENG KABUPATEN BONE - Sudirman; Sitti Rahmi; Irmawati Astaman (STKIP Subang, 2026)
This study aimed to improve the science and social studies (IPAS) learning outcomes of fourth-grade students at SD Inpres 4/82 Abbumpungeng, Cina District, Bone Regency through the application of the simulation learning method. The study used a qualitative approach with classroom action research conducted in two cycles. The subjects were the fourth-grade teacher and 15 students, consisting of five male and ten female students. Data were collected through observation sheets, learning outcome tests, and documentation. Data analysis was conducted through data reduction, data presentation, conclusion drawing, and verification. The findings showed that the implementation of simulation learning improved the learning process and student achievement. Teacher activity increased from 80% in Cycle I to 100% in Cycle II, while student activity increased from 66.67% in Cycle I to 86.67% in Cycle II. Student learning completeness also increased from 4 students (26.67%) in Cycle I with an average score of 67 to 12 students (80%) in Cycle II with an average score of 82. These results indicate that simulation learning can create active, contextual, and meaningful learning experiences. Therefore, the simulation method can be used as an alternative strategy to improve IPAS learning outcomes in elementary school.